130k views
0 votes
F(x)=2x-4. F(x)=2x-4 f-1x=_x+_. Complete the inverse function

1 Answer

5 votes

Answer:


f^(-1)(x) = (1)/(2)(x +4)

Explanation:

Given


f(x) = 2x - 4

Required

Determine the inverse function

Start by replacing f(x) with y


y = 2x - 4

Swap the positions of y and x


x = 2y - 4

Make y the subject: Add 4 to both sides


x+4 = 2y - 4+4


x+4 = 2y

Make y the subject: Divide through by 2


(1)/(2)(x + 4) = y


y = (1)/(2)(x + 4)

Replace y with f-1(x)


f^(-1)(x) = (1)/(2)(x +4)

User Dustin Michels
by
5.2k points